2022
DOI: 10.1108/meq-10-2021-0235
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of on-demand ridesharing: the role of awareness of environmental consequences

Abstract: PurposeThe primary goal of this study is to determine the predictors of on-demand ridesharing intention in an emerging economy. For this purpose, the study uses the theoretical underpinnings of the theory of planned behavior (TPB).Design/methodology/approachThe study surveyed 347 frequent users of ridesharing services using a set of pre-validated scales. The resulting data were analyzed using covariance-based structural equation modeling (CB-SEM).FindingsThe results of SEM analysis disclosed that the significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 106 publications
(249 reference statements)
0
16
0
Order By: Relevance
“…Meanwhile, Javid et al (2022) show an influence of awareness of traffic on behavioral control toward drivers speeding behavior in Lahore based on the TPB theory of Fishbein and Ajzen (1975). A positive relationship between individual awareness of environmental consequences and behavioral control and intention is found in a study on sustainable development by Sajid et al (2022). Among Chinese university students, an explicit perception such as gratitude might boost self-esteem (Kong et al, 2015).…”
Section: H2a: Implicit Perception Of the Rich Has A Negative Influenc...mentioning
confidence: 94%
See 1 more Smart Citation
“…Meanwhile, Javid et al (2022) show an influence of awareness of traffic on behavioral control toward drivers speeding behavior in Lahore based on the TPB theory of Fishbein and Ajzen (1975). A positive relationship between individual awareness of environmental consequences and behavioral control and intention is found in a study on sustainable development by Sajid et al (2022). Among Chinese university students, an explicit perception such as gratitude might boost self-esteem (Kong et al, 2015).…”
Section: H2a: Implicit Perception Of the Rich Has A Negative Influenc...mentioning
confidence: 94%
“…Previous studies have demonstrated the impact of individual awareness on behavioral control (Fishbein & Ajzen, 1975 ; Sajid et al, 2022 ). For example, Han ( 2015 ) demonstrates the prominent role of awareness of consequences on behavioral control and tourist intention.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Other than attitude, subjective norm was the other variable which included within the framework of TPB as another variable which could have a significant impact toward consumers or individuals' intention and actual decision to perform certain behaviors (Obrenovic et al, 2022;. Subjective norm itself could be understood as all forms of social pressures which were subjectively perceived or felt by the individuals, in which these pressures from their peers, colleagues, or the other people within the society could actually determine whether or not certain behaviors will be performed by these individuals or not (Jose and Sia, 2022;Alimoradi et al, 2022;Laguia et al, 2022;Sajid et al, 2022). In this case, individuals' subjective perception regarding how their peers, friends, colleagues, family or societies in general perceive or judge their behavior will eventually cause them to thoroughly evaluate the behavior that they want to perform.…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Environmental awareness is considered as one of the main motivators of individuals to behave environmentally in the environmental psychology literature (Arkorful, 2022;Bagla et al, 2022;Ogiemwonyi et al, 2020;Sajid et al, 2022). Environmental awareness is the collection of ideas regarding the relationship between human beigns and the Nature which is the prerequisite of the idea of proenvironmental behaviors.…”
Section: Lack Of Environmental Awarenessmentioning
confidence: 99%
“…Barriers at level 5 of the ISM model lead to the other fundamental barriers at level 4 including managerial complexity, lack of environmental awareness, lack of necessary technical skills and knowledge, and lack of infrastructure. People's ignorance of sustainable behavior is a crucial factor in the lack of environmental awareness (Sajid et al, 2022). In other words, unless people understand how and why green computing efforts should be implemented, investing in them is meaningless.…”
mentioning
confidence: 99%